Central vs. brachial blood pressure and pulse pressure amplification for mortality risk prediction in patients undergoing coronary angiography - Daschner, Clara; Kleber, Marcus E.; Ayasse, Niklas; Stach-Jablonski, Ksenija; Yücel, Gökhan; Husain-Syed, Faeq; Niessner, Alexander; Krüger, Bernd; März, Winfried; Krämer, Bernhard; Yazdani, Babak (American journal of hypertension, 2025)
Arterial hypertension is a significant risk factor for cardiovascular (CV) morbidity and mortality. Although central blood pressure (BP) evaluation is considered the gold standard, the reliability of non-invasive measurements remains unclear. Therefore, we compared the predictive value of invasively measured central BP with non-invasively measured brachial BP and analyzed pulse pressure (PP) amplification (delta-PP; the difference between central and peripheral PP) as an independent predictor of mortality.We analyzed systolic BP (SBP), diastolic BP (DBP), mean arterial BP (MAP), PP, and delta-PP as predictors of CV and all-cause mortality in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study, involving 3,316 patients referred for coronary angiography.All brachial BP parameters, except DBP, were significantly linked to all-cause and CV mortality in a univariate analysis. A 10 mm Hg increase in SBP, MAP, and PP corresponded to increased risks of all-cause (11%, 10%, and 19%) and CV mortality (11%, 11%, and 18%). Central SBP and PP showed similar, but numerically weaker, associations with increased risks of all-cause (5% and 10%) and CV mortality (4% and 8%). After adjusting for age, sex, body mass index, diabetes mellitus, and eGFR, only delta-PP independently predicted mortality with a 10 mm Hg increase linked to a 4% reduction in all causes and a 6% reduction in CV mortality.Neither brachial nor centrally measured BP parameters were independent mortality predictors in contrast to PP amplification, which remained an independent predictor of mortality in multivariate analysis, in a cohort with a medium to high CV risk profile. As PP amplification decreased, mortality increased.
Online veröffentlicht: 19. Dezember 2024
Gesehen am 11.06.2025